TC14012 enhances the anti-fibrosis effects of UC-MSCs on the liver by reducing collagen accumulation and ameliorating inflammation - Fan Ding; Yuting Liu; Jia Li; Xiao Wei; Jiangdong Zhao; Xiaojing Liu; Liqiang Zhang (Stem Cell Research & Therapy, 2024)
Abstract Background Mesenchymal stem cells (MSCs) are attracting attention as a promising cell-based therapy for the treatment of liver fibrosis or cirrhosis. However, the strategies and potential mechanisms of MSCs therapy need further investigation. The CXCL12/CXCR4/CXCR7 chemokine axis is well known to regulate cell migration and is involved in the regulation of liver fibrosis. This study aims to treat MSCs with a CXCR7-specific agonist to evaluate its therapeutic effects on hepatic fibrosis and potential mechanisms. Methods TC14012, a potent agonist of CXCR7, has been used to pretreat human umbilical cord-derived MSCs (UC-MSCs) and assess its effect on proliferation, apoptosis, migration, immunoregulation, and gene regulatory network. Then, CCl4-induced liver fibrosis mice models were used to evaluate the therapeutic effect and mechanism of TC14012-treated UC-MSCs for treating hepatic fibrosis. Results TC14012 increased CXCR7 expression in UC-MSCs. Notably, co-culture of liver sinusoidal endothelial cells (LSEC) with TC14012-pretreated UC-MSCs increased CXCR7 expression in LSEC. Additionally, TC14012 promoted cell migration and mediated the immunoregulation of UC-MSCs. Compared to UC-MSCs without TC14012 pretreatment, UC-MSCs treated with TC14012 ameliorated live fibrosis by restoring CXCR7 expression, reducing collagen fibril accumulation, inhibiting hepatic stellate cells activation, and attenuating the inflammatory response. Conclusion This study suggests that TC14012 pretreatment can enhance the therapeutic effects of UC-MSCs on liver fibrosis, mainly by promoting the migration and immunoregulation of MSCs.